The effects of a short-term (1-week) very low-calorie diet (850 calories) comparing low and normal protein content on cardiometabolic outcomes, glucose metabolism and autophagy - Burns, Lucy (2025)
Background and Aims. Dietary restriction in healthy adults has been shown to promote cardiometabolic health and autophagy; the degradation and recycling of damaged and dysfunctional cytoplasmic contents. Low protein diets may further stimulate autophagy through mTOR inhibition mediated by low amino acid availability. This project aims to investigate the effects of a 7-day nutritional intervention in healthy humans using very low-calorie (VLCD), fasting-mimicking plant-based diets with low and high protein content on cardiometabolic outcomes, body composition, molecular markers of autophagy and ER-stress, and gut microbiome health.